Imagining Sustainable Futures: The Transformative Potential of Green Immersive Virtual Reality Experiences (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
This essay examines the transformative im- pact of Green Immersive Virtual Reality (IVR) experiences designed by artists to spread environmental literacy and societal change. Through methodologies like Critical Dis- course Analysis (CDA) and Lars Elleström’s framework, it analyzes the immersive artwork Of Hybrids and Strings (2021) by Lauren Moffatt to investigate if and how Green IVR challenges existing structures of thought while fos- tering alternative modes of being. By immersing users in multisensory virtual environments and incorporating in- termedial connections with tangible artifacts, experiences prompt participants to reimagine their relationship with the natural world and envision more sustainable futures. Ultimately, the study highlights Green IVR as one of the catalysts for environmental literacy and societal change, emphasizing its role in shaping collective imagination and inspiring meaningful engagement with ecological issues.
Keywords: Immersive experience; Virtual reality; Green media; Interactive media; Environmental literacy